"It's a big adjustment coming from the reserve to living in a totally different society": Exploring the well-being of First Nations athletes playing sports in an urban mainstream context. (March 2020) - Johnson, Shara R.; Crosschild, Tarrant; Poudrier, Jennifer; Foulds, Heather J.A.; McHugh, Tara-Leigh; Humbert, Louise; Ferguson, Leah J.
Abstract: Indigenous athletes living in remote or rural areas, interested in pursuing sport at elite levels, often relocate from their home communities to urban "mainstream" centres. The purpose of this qualitative case study was to explore the psychological well-being and multicultural adjustment experiences of two relocating First Nations athletes. Conversational group interviews and photovoice reflections were adopted to hear stories from six participants: two First Nations female siblings who relocated from a rural First Nation community to pursue hockey, the athletes' parents, and the athletes' billet parents. Five themes were created to explain how the athletes adjusted and strove to flourish in their new environment: (1) Interconnected webs of support; (2) Managing emotional challenges; (3) Progressing during setbacks; (4) Comfort in new environments; and, (5) Maintaining cultural connections. Findings suggest that First Nations athletes who relocate from their home communities may require a robust support network and nurturing environment to flourish in an urban mainstream sport context. Highlights: Emotion regulation is a key coping strategy athletes and parents use during relocation. Maintaining cultural connections is significant to athletes' overall well-being. Indigenous athletes use available support networks as a communal coping resource. Adjusting requires a collaborative effort from various stakeholders.